Nestin Expression Identifies Ependymoma Patients with Poor Outcome - Milde, Till (Brain Pathol, 2012)
Ependymomas are primary brain tumors found throughout the central nervous system (CNS) in children and adults. Currently, many treatment protocols stratify grade I and II ependymomas as low‐risk tumors, whereas grade III anaplastic ependymomas are considered high‐risk tumors. The prognostic significance of World Health Organization (WHO) grade II or III, however, remains debated, and it is furthermore increasingly recognized that the pathologic differentiation between grades II and III is arbitrary in daily practice, thus resulting in imprecise risk stratification. Therefore, prognostic markers enabling more precise stratification to guide treatment decisions are urgently needed. An analysis of n = 379 tumor samples revealed that protein expression of nestin, a marker for neural stem and progenitor cells established as a routine staining in most neuropathology centers, is associated with poor outcome in intracranial ependymomas. Most importantly, nestin‐positive grade II ependymomas have the same prognosis as grade III ependymomas. Multivariable analysis demonstrates that nestin positivity is an independent marker for poor progression‐free survival (PFS) and overall survival (OS). Gene expression analysis for transcriptionally co‐regulated genes revealed a strong association of developmental and epigenetic processes with nestin. In summary, our data implicate nestin as a useful novel marker for intracranial ependymoma risk stratification easily implementable in routine diagnostics.